SOCIAL-EMOTIONAL DEVELOPMENT OF CHILDREN FROM THE PERSPECTIVE OF ECOLOGICAL SYSTEMS THEORY AND SCHOOL READINESS: A PARTICIPATORY ACTION RESEARCH CASE STUDY - Hidjanah,,, Hidjanah; Dtakiyyatuddaaimah, Dtakiyyatuddaaimah; Irna, Irna (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
Teacher and parent involvement with children has been associated with a number of adaptive characteristics in preschool children, and the relationship between family and teacher is an important contributor to school readiness. This study reports a participatory, teacher-parent involvement case study approach designed to facilitate school readiness among disadvantaged preschool children, with a particular focus on social-emotional stimulation. The study aimed to extend the study of social-emotional development from ecological systems theory to the context of children's school readiness, stimulating (1) familiarity with the school environment, (2) adjustment, (3) displaying habits of independence and (4) helping behavior, and (5) tolerance. The study, conducted over a 12-month period, observed specific interpersonal competencies (i.e., attachment, initiative, and anxiety/withdrawal), in contrast, differences in the extent to which positive action was given to children experiencing behavioral problems (i.e., anger/aggression, self-control, or conduct problems) as a function of being prepared to be given action. With participants of the principal, group B teachers, who were willing to 44 children voluntarily participate in this study, Data for this study included field notes, non-participant and participant observations, curriculum documentation, focus group and individual interviews, reflective journals/diaries, and photovoice. Data were analyzed qualitatively and quantitatively using thematic analysis and narrative inquiry-based analysis. The contribution of this study can be used as input for policy makers, parents, PAUD teachers, and the community in Indonesia. The implications of this intervention appear to be very effective in building social-emotional competencies beyond the impacts experienced as a function of participation in the early school entry program. Limitations and implications for research can be reviewed for the future.